Pathways to Korean culture paintings of the Joseon Dynasty, 1392-1910 - Jungmann, Burglind (Reaktion Books, 2014)
Introducing the major works and currents of Joseon painting, Pathways to Korean Culture explores the various social, cultural and political perspectives of this dynamic, dynastic era (1392-1910), uncovering the fascinating history of more than 500 years of Korean art and visual culture. In this book Burglind Jungmann examines an array of themes and aspects of the art world of the Joseon dynasty, from the ink painting tradition of the literati elite to the role of women as both patrons and artists. She looks at the various roles of paintings in Joseon Korea, where they were as important for foreign exchange as they were as a means of escapism, and she explores the dynasty's overarching Confucian ideology, which was constantly at odds with the culture's Buddhist projects. The book investigates select clusters of objects to shed light on the multiple layers of personal, intellectual, aesthetic, religious, sociopolitical and economic contexts in which they are embedded.From palace decorations to established artworks, this book takes a sweeping, comprehensive look at Korean culture and history, exploring its engagement with the West, its political affiliations with China and its unique range of artists. -- Descripción de http://www.bookdepository.com/Japan-Journeys-Andreas-Marks/9784805313107 (June 26, 2015).